CYBER CRIME AND THE SOCIOLOGICAL IMPLICATION IN THE NIGERIA'S TERTIARY EDUCATION SYSTEM - Suleiman, Ahmad, A. (FUDMA Journal of Sciences, 2023)
The global infrastructure on information renders a vast and unlimited access for a lot of organizations and individuals to do bulk of activities. This made it on the increase among anonymous hoodlums termed as ‘cyber criminals’. The nature, type, mode, count, cost, and dynamical sophistication of such attacks are seriously increasing and it is so alarming. Nigeria is even rated 3rd globally in cyber crime; although, it is a global phenomenon. Recently, one of the popular social sites Facebook, was hacked upon which 50 million accounts including that of the company’s chief executive were victims. There are limited academic write up and researches carried out on cyber security and cyber threat, which made it looks more professional than academic. This paper as a conceptual and discursive examines the categories, types, modes of cybercrime and the sociological implications of these kinds of crimes on or with cyber space which seems to be a serious threat to our entire security. The paper discusses on such activities in relation to universities system in Nigeria and outlined on the laws, measures and recommendations to address the cyber crime and cyber security in the country.
Keywords: Cyber Crime, Sociology, Education, Nigeria